Mobile Computing - Imielinski, Tomasz; Korth, Henry F. (Springer US, 1996)
The rapid development of wireless digital communication technology has cre ated capabilities that software systems are only beginning to exploit. The falling cost of both communication and of mobile computing devices (laptop computers, hand-held computers, etc. ) is making wireless computing affordable not only to business users but also to consumers. Mobile computing is not a "scaled-down" version of the established and we- studied field of distributed computing. The nature of wireless communication media and the mobility of computers combine to create fundamentally new problems in networking, operating systems, and information systems. Further more, many of the applications envisioned for mobile computing place novel demands on software systems. Although mobile computing is still in its infancy, some basic concepts have been identified and several seminal experimental systems developed. This book includes a set of contributed papers that describe these concepts and sys tems. Other papers describe applications that are currently being deployed and tested. The first chapter offers an introduction to the field of mobile computing, a survey of technical issues, and a summary of the papers that comprise sub sequent chapters. We have chosen to reprint several key papers that appeared previously in conference proceedings. Many of the papers in this book are be ing published here for the first time. Of these new papers, some are expanded versions of papers first presented at the NSF-sponsored Mobidata Workshop on Mobile and Wireless Information Systems, held at Rutgers University on Oct 31 and Nov 1, 1994
Keywords: Computer Science; Computer Communication Networks; Electrical Engineering; Computer Science, general; Computer science; Computer communication systems; Electrical engineering; Mobile Telekommunikation; Tragbarer Personal Computer; Aufsatzsammlung